New framework for parallel interconnection of buck converters: Application to optimal current-sharing with constraints and unknown load. (June 2019) - Trégouët, Jean-François; Delpoux, Romain
Abstract: In this paper, heterogeneous set of parallel buck converters, feeding an unknown resistive load via a common DC bus, is considered. When addressing control design problem of this interconnected power converter, one has to accommodate competing objectives of (i) voltage regulation and (ii) power distribution among branches, also called current-sharing in this context. Related dynamics being coupled, classical solution resorts to frequency separation to prevent undesirable interaction between them. In stark contrast with this approach, this paper proposes a novel framework which completely separate voltage regulation from current distribution dynamics without frequency separation, hence offering tractability without sacrificing performance. Such a reformulation is performed on the open-loop model so that control law candidates are not confined in some particular class. Arbitrary large set of heterogeneous converters can be handled. Remarkably, voltage regulation boils down to the control of a single virtual buck converter. Controller design example exploiting the new structure is provided. In the context of unknown resistive load, this controller achieves voltage regulation and minimizes overall power losses at the steady-state while taking current limits of each branch into account. Those results are supported by formal statements and proofs, and assessed through experimental results.